Developing thematic-integrative learning module with problem-based learning model for elementary school students - Monika Handayani (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
The study aims to (1) produce a integrative thematic learning module with PBL model which is viable, and (2) determine the effectiveness of the module towards the independent learning and learning outcomes of year five students of SD Negeri Pudjokusuman 1 Yogyakarta. This research was research and development. The subjects were teachers and students of year five students of SD Negeri Pudjokusuman Yogyakarta. Data analysis technique used paired sample t-test and independent sample t-test with significance level of 0.05. The results of this study are (1) an appropriate integrative thematic learning module with problem based learning model. The proof of feasibility of the product is based on the test results of matter experts, the media experts test, the response of the teachers, and the response of the students. (2) The result shows that the developed module is effective to improve student’s independent learning and learning outcomes. It is based on the results obtained in the field trials showing p 0.05 in cognitive learning outcomes and independent learning. Futhermore, based on the observation results student’s in affective and psychomotor learning outcomes of the students in experimental class have a higher percentage than of the control class.